Pendampingan UMKM Melalui Pemanfaatan Media Sosial Instagram Dalam Meningkatkan Segmentasi Pasar di Batik New Colet Jombang - Ma’rifah, Hikmah Nuraini; Azizah, Rina Avi Nur; Jordi, Mochamad Rizal; Amrullah, Mohammad Brillian Nuruddin; Ichsan, M. Nurul; Yunanto, Imron Febri; Dermawan, Riki Budi; Fatmah, Elysa Ayu (Welfare : Jurnal Pengabdian Masyarakat, 2023)
Social media that can be used to support the sale of goods online include Instagram,with various complete features on the application, namely business Instagram. Based On this, Sharia Finance Practice activities have been carried out in Jatipelem Village, Diwek District, and Jombang Regency, specifically in the Batik Tulis New Colet Small and Medium Enterprises (UKM) with Mr. Sutrisno as the owner. Writing this journal This articleaims to assist Batik New Cape Town SMEs in utilizing Instagram social media to support online marketing and find out customer segmentation so that they can add to their knowledge of business actors and increase business turnover. Method: In this article, data processing is carried out in several stages, namely literature study, interviews, and system analysis. The results of this discussion led to the conclusion that the use of social media for sales greatly influences the ease of promotion and interaction with customers. By utilizing Instagram, it is hoped that it will make it easier for Batik New Colet SMEs to see and observe community interactions through Instagram insight. The effect that is really felt actually occurs in the interactions ofInstagram users recorded on the personal Instagram accounts of business actors where the followers of these accounts began to find out about the batik products offered by business actors. By registering an Instagram account as a business account, Batik New Colet businesses can easily see insight into the number of followers.